From Eckhart to Ruusbroec : A Critical Inheritance of Mystical Themes in the Fourteenth Century - Kikuchi, Satoshi (Book collections on Project MUSE., 2014)
The mystical relationship between Meister Eckhart and Jan van Ruusbroec. In this thorough textual, historical, and doctrinal study the author seeks to clarify the relationship between two prominent mystics of the fourteenth century: Meister Eckhart, the German Dominican, and Jan van Ruusbroec, the Brabantine Augustinian. Special attention is paid to Ruusbroec's criticism of mystical tenets circulating in Brabant at that time which were both textually and doctrinally related to Eckhart's condemned propositions in the papal bull In agro dominico. This fact implies that Ruusbroec was confronted wi.